An Economic, Political and Industrial Strategy for Labour

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This policy document adopted by the Executive Council of the Canadian Labour Congress was ratified by the 12th Constitutional Convention held in Québec City, April 1978.